Electromagnetic interference shields on the basis of powdery waste gas cleaning cupola - O. V. Boiprav; M. R. Neamah; V. B. Sokolov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Results of researches of silt of the cupola gases clearing with the various fractions size influence on electromagnetic radiations easing on band 0,8 … 16 GHz are resulted. The expediency of using these materials for manufacturing of the broadband composite screens possessing, having small values reflexion and transfer factors, high processability and low cost are shown.